Diagnóstico de maturidade tecnológica de micro e pequenas empresas da indústria AEC para implementação da engenharia simultânea - Gevaerd, Paulo Henrique Ferrarini (2017)
This research presents an analysis of maturity and also the impact of computational tools in architecture, engineering and construction enterprises, in relation to the objectives of Concurrent Engineering. The main objective was to understand the impact on the technological maturity of small enterprises in the architecture, engineering and construction industry when using collaborative computational tools in the implementation of Concurrent Engineering concepts. To develop the research, bibliometric analyses were carried out to characterize the main authors involved with the themes Concurrent Engineering and Collaborative Systems for construction industry. These authors formed the theoretical basis for the development of the interview protocol in multiple case studies. After the elaboration of the research protocol and its improvement from a pilot study, interviews were conducted with nine enterprises in the sector and from their answers the maturity analyses and systems requirements were developed. Based on the analyses, the following conclusions were obtained: small enterprises need greater self-knowledge to balance their business maturity; architecture enterprises have a differentiated technological maturity profile of engineering and construction enterprises; architectural enterprises are positively influenced by their tools, engineering and construction enterprises still have low levels of maturity in these relationships; the tools used by enterprises today, for the most part, do not assist in the integration of company processes and between enterprises, which makes it difficult to implement the concepts of Concurrent Engineering. In addition, were proposed: simultaneous flow of activities between small enterprises, systems for the implementation of Concurrent Engineering concepts and guideline for implementation of the systems in the companies interviewed.